Establishing a registry of children and young people with diabetes in north east England and north Cumbria. (11th March 2013) - Blakey, Karen; Johnson, Gillian; McNally, Richard JQ; Court, Simon; Potts, Adam; Stephenson, Carolyn; Lamb, Bill; Cheetham, Timothy D
Abstract: The incidence of type 1 diabetes and type 2 diabetes in children and adolescents is rising. The associated public health burden is substantial with major implications for those involved in planning health care provision at all levels. The aetiology of diabetes in this age group is poorly understood, although both genetic and environmental factors are likely to be involved. Clinicians involved in the management of diabetes in the young in the Northern Region have wanted to establish a diabetes registry for more than two decades. With input and financial support from NHS Diabetes we have finally been able to establish a population‐based registry of all prevalent cases of diabetes diagnosed in children and young people (0–17 years) in north east England and north Cumbria. There are several unique features of the study region. Most notably, compared with other areas, it has little general outward migration and only includes a small ethnic minority community. We anticipate that the registry will provide an important regional data source for research, audit and service provision planning. The importance of regional registries is now being recognised, and we hope that a description of our recent experience will be useful to individuals involved in registry development elsewhere. Copyright © 2013 John Wiley & Sons.